The Voice of Silent Classrooms: A Qualitative Study on the Educational Invisibility of Introverted Students - Ethem Gürhan (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2026)
This qualitative study investigates the phenomenon of educational invisibility experienced by introverted students in elementary school classrooms, where participation is often narrowly defined through verbal expression and social assertiveness. Using a case study approach, data were collected through semi-structured interviews with 12 elementary school students and 4 classroom teachers in Türkiye, complemented by unstructured classroom observations conducted over eight weeks. Thematic analysis revealed five key themes: Invisible participation, learning through silence, avoidance of social pressure, teacher attitudes and expectations, and the restrained desire to express oneself. The findings indicate that introverted students are cognitively and emotionally engaged yet frequently marginalised by classroom norms that privilege overt verbal participation. Practical implications include redesigning teacher education programs to address personality-based differences in participation, employing nonverbal assessment tools, and adopting inclusive classroom management strategies in basic education.